Single Balloon Enteroscopy for Endoscopic Retrograde Cholangiography in a Patient with Hepaticojejunostomy after Liver Transplant. (5th May 2010) - Di Pisa, Marta; Miraglia, Roberto; Volpes, Riccardo; Gruttadauria, Salvatore; Traina, Mario
Abstract : We report a case of a post-transplant patient with hepaticojejunostomy in whom we used a single balloon enteroscopy to access the biliary tree. This procedure seems to be safe and feasible for approaching the biliary anastomosis by means of the overtube and fixation of the small bowel by the balloon.